Decreased Ceftriaxone Susceptibility in Emerging (35B and 6C) and Persisting (19A) Streptococcus pneumoniae Serotypes in the United States, 2011-2012: Ceftaroline Remains Active In Vitro among β-Lactam Agents - Mendes, Rodrigo E. (American Society for Microbiology, 2014)
Totals of 8.7% (103/1,190) and 21.0% (249/1,190) of the Streptococcus pneumoniae isolates recovered from specimens collected in the United States during the 2011-2012 AWARE (Assessing Worldwide Antimicrobial Resistance Evaluation) Surveillance Program were ceftriaxone nonsusceptible according to the CLSI (≤1 μg/ml for susceptible) and EUCAST (≤0.5 μg/ml for susceptible) criteria, respectively. Decreased susceptibility to ceftriaxone (MIC, 1 μg/ml) was frequently observed among serotypes 19A (51.4%; 128/249) and 35B (29.7%; 74/249), which were most often observed in the East South Central and South Atlantic U.S. Census regions. Ceftaroline (MIC(50/90), 0.12/0.25 μg/ml) remained active (≥96.8% susceptible) when tested against these less susceptible isolates.